Pemanfaatan Internet Dalam Pengembangan Usaha Kuliner Desa Daruba Kecamatan Morotai Selatan - Posu, Risaldi; Latief, Fandi (Jurnal Ilmiah Wahana Pendidikan, 2026)
The use of the internet by entrepreneurs and the community in Daruba Village, South Morotai District, Morotai Island Regency, has built a symbiotic mutualistic communication relationship or a mutually beneficial relationship. The internet functions as a communication medium for ordering food and also promoting food sold by entrepreneurs. The internet in business is used for information exchange, product catalogs, promotional media, electronic mail, bulletin boards, electronic questionnaires, and mailing lists. The internet can also be used for dialogue, discussion, and consultation with consumers online, so that consumers can be proactively and interactively involved in the design, development, marketing, and sale of products. The research used qualitative research methods. In this study, it is clear that the communication that is built can form an interaction, namely social interaction. Social interaction can occur when there is social contact and communication between two individuals or groups. Social contact is the first stage of the occurrence of social relations. Communication is the delivery of information and the provision of interpretation and reaction to the information conveyed. Karp and Yoels point out several things that can be sources of information for the initiation of communication or social interaction.